LRR-RLK subfamily II of coreceptors: emerging, non-canonical and canonical roles in plant antiviral immunity and development - Sampaio, Fellipe R.; Takagaki, Beatriz M.; Breves, Sâmera S.; Rodrigues, Raquel G.; Neves, Viviano G. O.; Ferreira, Félkerson M.; Ribeiro, Nathália G. A.; Santos, Eulálio G. D.; Reis, Pedro A. B.; Fontes, Elizabeth P. B. (Frontiers in Plant Science, 2025)
Coreceptors act together with receptors in the process of signal transduction. Within the LRR-RLK subfamily II, coreceptors play an essential role by serving as a connection between growth and immunity in plants. The 14 LRRII-RLK identified genes in Arabidopsis have been phylogenetically clustered in four closely related groups. Three of them have been functionally characterized: (i) NIKs, which are associated with responses to viral infections, (ii) SERKs, which are involved in both development and immunity, and (iii) CIKs, which are connected to homeostasis, growth, and meristem development, as well as to a lesser extent, immunity. Currently, LRRII-RLKs have been more intensively investigated as potential antiviral mechanisms due to their emerging roles in antiviral immunity and their potential of being targeted by viral manipulation. Despite their partial functional redundancy and interactions in immunity and developmental signaling mechanisms, targeting LRRII-RLKs through genetic manipulation may lead to the development of a broad-spectrum resistance to viral infections, while also preserving plant growth and yield.